A review on III–V core–multishell nanowires: growth, properties, and applications. (7th March 2017) - Royo, Miquel; De Luca, Marta; Rurali, Riccardo; Zardo, Ilaria
Abstract: This review focuses on the emerging field of core–multishell (CMS) semiconductor nanowires (NWs). In these kinds of wires, a NW grown vertically on a substrate acts as a template for the coaxial growth of two or more layers wrapped around it. Thanks to the peculiar geometry, the strain is partially released along the radial direction, thus allowing the creation of fascinating heterostructures, even based on lattice mismatched materials that would hardly grow in a planar geometry. Enabling the unique bridging of the 1D nature of NWs with the exciting properties of 2D heterostructures, these novel systems are becoming attractive for material science, as well as fundamental and applied physics. We will focus on NWs made of III–V and III–V-based alloys as they represent a model system in which present growth techniques have reached a high degree of control on the material structural properties, and many physical properties have been assessed, from both the theoretical and experimental points of view. In particular, we provide an overview on the growth methods and structural properties of CMS NWs, on the modulation doping mechanisms enabled by these heterostructures, on the effects of a magnetic field, and on the phononic and optical properties typical of CMS NWs. Moreover, we review the main technological applications based on these systems, such as optoelectronic and photovoltaic devices.